MODELLING UNSATURATED FLOW IN AN EVOLVING KARST AQUIFER - Kaufmann G. (My University, 2003)
A two-dimensional cross-section of a karst aquifer, in which chemical dissolution enlarges fractures with time, is studied. The karst aquifer is recharged by precipitation and drains towards a resurgence. The initial aquifer has low conductivities both in the rock matrix and the fracture network, and the initial water table is high. As the enlargement of fractures by dissolution increases the fracture conductivity, the water table drops, until it reaches a steady-state along the level of the resurgence. Several parameterisations are discussed for flow in the unsaturated zone above the water table. It is shown that different approaches result in similar cave passage patterns, with a large water-table cave draining the recharge towards the resurgence. However, flow patterns in the unsaturated zone can be very different for the different parameterisations.
Keywords: KARST AQUIFER; LIMESTONE DISSOLUTION; CAVE GENESIS; HYDRAULIC CONDUCTIVITY